Twenty-two years a slave and forty years a freeman : embracing a correspondence of several years while president of Wilberforce Colony, London, Canada West /: embracing a correspondence of several years while president of Wilberforce Colony, London, Canada West. ([2012]) - Steward, Austin, 1794-1860
No abstract available